Return on investment of internet delivered exposure therapy for irritable bowel syndrome: a randomized controlled trial - Wallén, Hugo (BMC Gastroenterol, 2021)
BACKGROUND: Irritable bowel syndrome (IBS) is a debilitating and costly disorder. Cognitive behavior therapy (CBT) is effective in the treatment of IBS, both when delivered over the internet and in face-to-face settings. CBT consists of different components and little is known about their relative importance. We have in an earlier study showed that inclusion of exposure in the CBT for IBS makes it even more effective. In the present study we wanted to evaluate the economic effects for society of inclusion vs exclusion of exposure in an internet delivered CBT for IBS. METHODS: We used data from a previous study with 309 participants with IBS. Participants were randomized to internet delivered CBT with (ICBT) or without exposure (ICBT-WE). We compared direct and indirect costs at baseline, after treatment, and 6 months after treatment (primary endpoint; 6MFU). Data was also collected on symptom severity and time spent by therapists and participants. The relative Incremental Cost Effectiveness Ratio (ICER) was calculated for the two treatment conditions and the return on investment (ROI). RESULTS: Results showed that ICBT cost $213.5 (20%) more than ICBT-WE per participant. However, ICBT was associated with larger reductions regarding both costs and symptoms than ICBT-WE at 6MFU. The ICER was − 301.69, meaning that for every point improvement on the Gastrointestinal Symptom Rating Scale—IBS version in ICBT, societal costs would be reduced with approximately $300. At a willingness to pay for a case of clinically significant improvement in IBS symptoms of $0, there was an 84% probability of cost-effectiveness. ROI analysis showed that for every $1 invested in ICBT rather than ICBT-WE, the return would be $5.64 six months after treatment. Analyses of post-treatment data showed a similar pattern although cost-savings were smaller. CONCLUSIONS: Including exposure in Cognitive Behavior Treatment for IBS is more cost-effective from a societal perspective than not including it, even though it may demand more therapist and patient time in the short term. TRIAL REGISTRATION: This study is reported in accordance with the CONSORT statement for non-pharmacological trials [1]. Clinicaltrials.gov registration ID: NCT01529567 (14/02/2013).